An Sartrean model for decision making: how to keep integrity in case of moral dilemma - Cherré, Benoît (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
In the modern world of enterprise, ambiguity and complexity are current factors, which managers have to take into consideration in their daily duties. Ethical dilemma represents the critical incident that challenges Human Resources Manager’s (HRM) values and his conceptions of ethics (Latif, 2001). Ethical Dilemma will often involve an apparent conflict between moral imperatives, in which to obey one would result in transgressing another (Miao-Ling, 2006). With a dilemma, the individual identity is challenged by one or the other choice and cannot endure it any longer. Dilemma represents a higher risk of losing the individual integrity. In this case, how to cope with integrity when facing ethical dilemma? French Philosopher Sartre advocates for the necessity of thinking ethics through dilemma and his philosophy places freedom and authenticity in the center of human identity and rejects all kind or form of determinism (Sartre, 1948 et 1992). Nowadays, many researches argue for the use of this perspective as a grid to understand and to promote ethical decision making (West, 2008). The usefulness of Sartre’s work is to bring a frame for ethical decision making in the case of a dilemma. We will make an updated review on contributors and specialists of Sartre philosophical writing in order to clarify some concepts and elements of his thoughts applied in Business Ethics and ethical decision-making (Jackson, 2005). In summary, any choice can be authentic as long as it is lived with a clear awareness of its contingency and responsibility (Sartre, 1948 and 1992). Sartrean ethics stressed on freedom over alienation, authenticity over bad faith and moral responsibility over cowardice (Sartre, 1948 and 1992). With our conceptual model, we try to demonstrate that Sartrean existentialism perspective can represent a description of the genuine ethical dilemma faced by HRM at workplace for which ethical stakes are challenged. We focused on an exploratory study by interviewing 47 Human Resources Managers (HRM) from Quebec (Canada). By analysing their speech with Atlas Ti softwar categorizing a form their, we were able to categorize some elements of their making decision-making. In our outcome, HRM did mention the presence of a particular ethical dilemma situation that which presents the characteristics of a «genuine moral dilemma», this situation implies the lay off of employee (Lemmon, 1962). Our findings illustrate which ethical elements or demands can cause ethical interrogation and psychological tension as anxiety. Some dialectical/opposed attitudes can be adopted while facing this HR dilemma: one can choose to be free by privileging moral creativity and authenticity meanwhile another can be alienated by showing some bad faith. Within the interviews, most HRM expressed or demonstrated that the first strategy, reaching authenticity, is the path to preserving personal project and moral responsibility towards employees. The search for authenticity based on freedom in their decisionmaking confirms some previous conceptual research (Jackson, 2005). Meanwhile, the second strategy can be damageable for the meaning of personal ethics. We found that freedom is an ultimate value that HRM claimed to use to preserve their individual integrity during the process of decision (Sartre, 1948). We notice above all that individual freedom and moral imagination are the best ethical attitudes to choose within a dilemma situation. The contribution of the Sartre’s ethics is a humanistic approach because it places human in the center of its concerns and gives them some tools to preserve their integrity and avoid ethical suffering. We end our presentation by displaying the practical usefulness of this model on our actual exploring research on HRM ethical leadership.